2012
DOI: 10.1073/pnas.1121400109
|View full text |Cite
|
Sign up to set email alerts
|

Modeling hepatitis C virus infection using human induced pluripotent stem cells

Abstract: Human pathogens impact patient health through a complex interplay with the host, but models to study the role of host genetics in this process are limited. Human induced pluripotent stem cells (iPSCs) offer the ability to produce host-specific differentiated cells and thus have the potential to transform the study of infectious disease; however, no iPSC models of infectious disease have been described. Here we report that hepatocyte-like cells derived from iPSCs support the entire life cycle of hepatitis C vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(176 citation statements)
references
References 25 publications
2
173
0
1
Order By: Relevance
“…7). Among these, the hepatocytespecific genes AFP, ALB, and GC, a member of the albumin gene family, were upregulated, suggesting that Huh7.5.1-8 cells have more differentiated hepatocytelike phenotypes that are favorable for HCV infection (15,29,(34)(35)(36). Girard et al previously showed that NTS is highly upregulated in HCV NS5A-expressing Huh7 cells (37) and may be associated with efficient HCV replication.…”
Section: Discussionmentioning
confidence: 99%
“…7). Among these, the hepatocytespecific genes AFP, ALB, and GC, a member of the albumin gene family, were upregulated, suggesting that Huh7.5.1-8 cells have more differentiated hepatocytelike phenotypes that are favorable for HCV infection (15,29,(34)(35)(36). Girard et al previously showed that NTS is highly upregulated in HCV NS5A-expressing Huh7 cells (37) and may be associated with efficient HCV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the first iPSC model of human liver infectious disease has also been reported recently. Schwartz and the colleagues reported that human iPSChepatocytes could support the entire life cycle of hepatitis C virus (HCV) including inflammatory responses to the viral infection (Schwartz et al, 2012). This study did not only offer a novel infectious disease model to study HCV pathogenesis, but also enabled future research regarding how host genetics could impact viral infection using personalized iPSC models.…”
Section: Human Ipsc Derived Hepatocytes For Disease Modelingmentioning
confidence: 99%
“…The experimental conditions used to generate MPCCs, maintain iPSCs, and differentiate iHeps have all been previously described (12,15,16,19). For HBV infection of MPCCs and iHeps, cultures were pretreated for 24 h with dimethyl sulfoxide [0.01% (vol/vol)], JAKi (1 μM; EMD Millipore), TBK1 inhibitor (1 μM; EMD Millipore), IFN-β (1,000 U/mL; R&D Systems), or entecavir (120 nM; Cayman Chemicals), as indicated, followed by infection with HBV + patient plasma.…”
Section: Methodsmentioning
confidence: 99%
“…As a complementary approach that enables more facile genetic manipulation on an untransformed and isogenic hepatocyte background, we also sought to establish robust HBV infection in induced pluripotent stem cell (iPSC)-derived hepatocyte-like cells (iHeps) (15,16). These cells have demonstrated their utility for modeling inherited metabolic disorders (17), incorporating genetic manipulations (18), and supporting infection with HCV (19)(20)(21). During iHep generation, the progression of differentiation is characterized by the sequential emergence of various hepatocyte-specific host factors known to play a role in the HBV life cycle, such as the transcription factor HNF4α and the nuclear receptor RXR (22).…”
Section: Significancementioning
confidence: 99%